Electron-Transfer Reaction of Cytochrome c Adsorbed on Mixed Alkanethiol Monolayer Electrode and Its Electrocatalytic Activity - Wang, Yu; Wan, Lingli; Song, Yonghai; Wang, Li (Asian Journal of Chemistry, 2012)
The electron-transfer kinetics of cytochrome c (cyt. c) immobilized on self-assembled monolayers modified gold electrode was demonstrated. Mixed monolayer films of 6-mercapto-1-hexanol and 11-mercaptoundecanoic acid are used to adsorb cytochrome c on the surface of gold electrode. These adsorbed cytochrome c molecules remained a dilute concentration on the mixed films. Electrochemical method and scanning tunneling microscopy technique was used to study the adsorbed protein. It showed a surface-controlled electrode process with the electron transfer rate constant of 65 s-1. The adsorbed cytochrome c maintained its activity and could also electrocatalyze the reduction of hydrogen peroxide, the Kmapp for this sensor was found to be 3.41 mM.